2011
DOI: 10.1097/lbr.0b013e318216da26
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Comparison of 2 Different Methods of Intrabronchial Lidocaine Delivery During Flexible Bronchoscopy

Abstract: This trial was registered with the Local Research Ethics Committee and with International Standard Randomised Controlled Trial Number.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…A comparison of lignocaine delivery either via the Enk device or via working channel of bronchoscope found that the mean duration of procedure was similar using either of the two techniques. [156] Administering topical lidocaine via nebulization using spray catheter allows lower requirement of the drug as compared to its delivery via a conventional syringe. In addition, lower doses of IV fentanyl were used with the spray catheter than with the syringe, although no differences in patient tolerance or safety were observed.…”
Section: Premedicationmentioning
confidence: 99%
“…A comparison of lignocaine delivery either via the Enk device or via working channel of bronchoscope found that the mean duration of procedure was similar using either of the two techniques. [156] Administering topical lidocaine via nebulization using spray catheter allows lower requirement of the drug as compared to its delivery via a conventional syringe. In addition, lower doses of IV fentanyl were used with the spray catheter than with the syringe, although no differences in patient tolerance or safety were observed.…”
Section: Premedicationmentioning
confidence: 99%
“…However, it might be difficult to obtain an even distribution of lidocaine in the bronchial system using this method, resulting in incomplete anesthesia of the airway walls. Therefore, spray catheters such as the Enk Fiberoptic Atomizer Set® have been developed, which allow nebulization of local anesthetics during the procedure [5]. The device mentioned was initially designed for use during awake fiberoptic intubation using oxygen flow for the nebulization of local anesthetics [6].…”
Section: Introductionmentioning
confidence: 99%
“…reported no benefit with use of nebulized lignocaine using a dedicated Enk device as compared with the conventional spray-as-you-go method. [17] On the contrary, Dreher et al . demonstrated reduction in lignocaine and fentanyl doses during bronchoscopy with nebulized lignocaine using Enk device as compared with spray-as-you-go method.…”
Section: Discussionmentioning
confidence: 99%